The Future of the Jews: How Global Forces are Impacting the Jewish People, Israel, and Its Relationship with the United States - Eizenstat, Stuart E. (Rowman & Littlefield Publishers, 2012)
In The Future of the Jews, Stuart E. Eizenstat, a senior diplomat of international reputation, surveys the major geopolitical, economic, and security challenges facing the world in general, and the Jewish world and the United States in particular. These forces include the shift of power and influence from the United States and Europe to the emerging powers in Asia and Latin America; globalization and the new information age; the battle for the direction of the Muslim world; nontraditional security threats; changing demographics, which pose a particular challenge for Jews worldwide and the rise of a new anti-Semitism that seeks to delegitimize Israel as a Jewish state. He also discusses the enduring nature of and challenges to the strategic alliance between the United States and Israel. Eizenstat’s provocative analysis will be of interest to everyone concerned about the future of Jews worldwide and in Israel and the United States’ role in a world that is confronting unprecedented simultaneous, cataclysmic changes.